Lean service and its implications in the quality of the service of the aircraft industry companies: A systematic review of the literature - Cabrera Bonilla, Jesus Orlando (2023)
Providing a high-quality service has become an important factor for the survival of companies and generating customer satisfaction, therefore airlines must improve the quality they offer in order to improve their image. There are various methods used to evaluate and optimize the quality of airline service, including lean tools. The purpose of this research is to determine what research has been carried out on the quality of service and lean service in the commercial aviation sector based on a systematic review of the literature, in order that airlines can evaluate future improvement proposals to avoid dissatisfaction generated and improve your profitability. The findings show the various dimensions that are related to lean service, giving rise to new studies, its link with the commercial aviation sector and other service areas. Likewise, lean service in this sector could be applied and focus on reducing check-in times at airports or reducing boarding times.